OPTIMALISASI PELAKSANAAN BUNKERING SHIP TO SHIP BERDASAR STANDAR STS TRANSFER CHECKLIST PT. PERTAMINA INTERNATIONAL SHIPPING - Ananda Kevin; Achmad Ali Mashartanto; Bayu Yudho Baskoro; Dody Efrianto; Pesta Fery A (STKIP Subang, 2026)
STS bunkering is the activity of supplying ship fuel through the ship-to-ship method. This study aims to optimize the implementation of STS bunkering based on the STS transfer checklist. The research method used is a qualitative descriptive method with data collection techniques of field observation, interviews, and documentation studies. The results of the study show that the factors hindering the fulfillment of the STS transfer checklist consist of several factors, including: lack of supervision on duty, damage and lack of equipment, errors in cargo handling, cargo contamination, manual sounding measurements, cargo contamination by water, high waves, and strong winds. These factors are interrelated and cause disruption to the fulfillment of the STS transfer checklist standards. Efforts made to overcome these obstacles include conducting routine STS drills, maintaining and providing equipment spare parts, implementing cargo circulation methods, conducting multiple soundings, monitoring cargo, and taking weather conditions into account before bunkering. With the implementation of these efforts, it is hoped that STS bunkering can be carried out optimally based on STS transfer checklist standards.